Anxiety, fear, and ontological security in world politics. Issue 2 (July 2020) - Kinnvall, Catarina; Mitzen, Jennifer
Abstract: This symposium addresses the role of anxiety, fear, and ontological (in)security in world politics. Proceeding from the recognition of the scholarly interest and multitude of approaches that characterize the field of ontological (in)security studies, the Symposium homes in on the relationship between anxiety and fear, and between anxiety, subjectivity, and agency. The Introduction critically engages with Anthony Giddens' understandings of ontological (in)security, in an effort to spur the revisiting, questioning, and, in some cases, leaving behind Giddens' assumptions in order to develop a more dynamic conception. In response, the first three contributions draw on resources in existentialist philosophy, especially Heidegger, Tillich, and Kierkegaard, to further unpack the relationship between anxiety and ontological (in)security. They do so by returning to the experiential moment of confronting existential anxiety, a moment that Giddens quickly closes down, to better grasp how existential anxiety resolves into an orientation to action. The final two essays, in comparison, bring anxiety 'back in' to locales where Giddens' theory occludes it: the unconscious and the international, thus arguing that emotional configurations other than fear are always possible.